Optimization of reactive power compensation in industrial facilities with photovoltaic distributed generation. - França, Kátia Kellen Martins de; Costa, José Adriano da (Latin American Journal of Energy Research, 2025)
The advancement of distributed photovoltaic generation in industrial environments has led to a significant reduction in electricity costs but has also changed the reactive power demand profile of installations. This shift can reduce the overall power factor (PF), leading to tariff penalties and overloading of the electrical system. This work presents an optimization model for PF correction in industrial consumers with photovoltaic generation, employing simplex linear programming to size and allocate fixed and automatic capacitor banks. The methodology considers multiple generation and demand scenarios, allowing reactive power compensation to be adjusted efficiently and economically. The study shows that the integration of photovoltaic plants can cause a significant reduction in PF during periods of high generation, requiring adaptable compensation strategies. The results indicate that applying the proposed model makes it possible to maintain the PF within the regulatory limits established by the Brazilian Electricity Regulatory Agency (ANEEL), avoiding penalties for excess reactive power and ensuring the economic benefits of distributed generation. The approach contributes to industrial energy planning by integrating renewable generation with reactive power correction techniques, enhancing both efficiency and system reliability.